2017
DOI: 10.3390/w9040247
|View full text |Cite
|
Sign up to set email alerts
|

Improved or Unimproved Urban Areas Effect on Soil and Water Quality

Abstract: Construction in urban areas usually results in compacted soil, which restricts plant growth and infiltration. Nutrients may be lost in storm runoff water and sediment. The purpose of this study was to determine if existing lawns benefit from aeration and surface compost additions without the negative impact of nutrient loss in runoff. Four sets of lawns were compared, with or without compost plus aeration, as a paired comparison. Surface bulk density was significantly reduced in the treated lawns (1.32 versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, it is important to consider a number of processes that can negatively influence the response of tree vigor to fertilization practices, such as nutrient leaching and soil compaction. For Logsdon and Sauer (2017), besides the superficial loss of nutrients from water runoff, compaction restricts plant growth by hindering water infiltration and aeration in the soil, which impairs solubilization of applied nutrients and consequently makes it difficult for trees to absorb them. Hobbie et al (2014) found that the leaves of Acer platanoides, Acer x fremanii, Fraxinus pennsylvanica, Quercus bicolor and Tilia cordata showed rapid decomposition, losing 80% of initial mass and releasing more than half of their phosphorus content after one year.…”
Section: Vegetative Vigormentioning
confidence: 99%
“…However, it is important to consider a number of processes that can negatively influence the response of tree vigor to fertilization practices, such as nutrient leaching and soil compaction. For Logsdon and Sauer (2017), besides the superficial loss of nutrients from water runoff, compaction restricts plant growth by hindering water infiltration and aeration in the soil, which impairs solubilization of applied nutrients and consequently makes it difficult for trees to absorb them. Hobbie et al (2014) found that the leaves of Acer platanoides, Acer x fremanii, Fraxinus pennsylvanica, Quercus bicolor and Tilia cordata showed rapid decomposition, losing 80% of initial mass and releasing more than half of their phosphorus content after one year.…”
Section: Vegetative Vigormentioning
confidence: 99%